Dikenga Dia Kongo, umbanda ancestralities in Curitiba - Wendell de Camargo, Hertz (2023)
Curitiba stands out in the field of Brazilian religions of Afro-indigenous matrix. Data report that the city contains about six thousand terreiros of umbanda. Based in the participant observation and visual dimension of the ethnographic method (photo record and video), applied between the years of 2016 and 2022, the research proposes to highlightrelated to the Kongo Cosmogram in the ceremonial opening rite of Terreiro Vovó Benta, in Curitiba, from the principles of Bantu-Kongo thought (FU-KIAU, 2001). In all these years, there were few changes in the diegetic structure of the rite that narrates the arrival of a warrior who summons other warriors to battle and leaves after fulfilling his mission. A closer look revealed that we are facing a fragment in dialogue with the Bantu-Kongo cosmology, which makes the religious experience - in the terreiro studied - symbolically more communicative and spectacular.